Characterization of Al-Ge anode materials for lithium-ion battery - Chua, Wen Jie (2014)
Al1-xGex was synthesized as potential high capacity anode materials for lithium ion secondary batteries using melt spinning process. Electrochemical properties of Al1-xGex (with x=2,4,7,8 ) were measured and their Li storage capabilities analyzed. The Al1-xGex with an Al:Ge ratio of 3:7 showed the best Li storage properties, with a stable capacity of 900mAhg-1 and 1823mAhcm-3 over 50 cycles, superior to Ge metal and other Al1-xGex compositions. Furthermore, a capacity of 544 mAhg-1 is still obtainable at 1C. Notably, in terms of cycling stability and rate performance, it surpasses current Al-based anodes reported in literature. This positions Al-Ge as a potential candidate for applications that not only require high gravimetric but also high volumetric capacity. To elucidate the possible reasons for the good Li storage properties, the first cycle electrochemical lithiation and de-lithiation behaviour of the Al1-xGex anodes were investigated by ex-situ XRD. Diffraction peaks of Al and Ge broadened and showed reduction in intensity upon cycling, indicating an increase in disorder and possible amorphization of the material. The lithiation and delithiation steps were also observed to be different from pure Al and pure Ge, which also plays a role in the improved performance. The nanocrystalline/amorphous phases and the deviation in the lithiation/de-lithiation mechanism suggest a synergetic effect which mitigated the huge volume variations and enhancing reaction kinetics.